The Post-Pandemic Inflation Debate: A Critical Review - Diogo Martins (PSL Quarterly Review)
This article offers a critical review of the post-pandemic inflation debate. The first section organizes the debate by categorizing the arguments into two broad perspectives: the neoclassical view and the critical political economy view, along with several subcategories. This classification is guided by the positions that participants in the debate took regarding the origins and propagation mechanisms of inflation, as well as the economic policy solutions proposed to address the current inflationary period. The second section highlights that the dominance of contractionary monetary policy as the primary response to contemporary inflation rests on weak foundations, with its theoretical and empirical justifications having been consistently and convincingly challenged by critical political economy circles over the past decades.